Assessing consumer consumption behaviour through social media marketing: a survey among youths in Malaysia / Mohd Remie Mohd Johan ... [et al.] - Mohd Johan, Mohd Remie; Yuan Li Mohd Zain, Elisya Maliha; Tomoki, Miura; Tee, Mcxin; Annuar, Nursyamilah (Universiti Teknologi MARA, Perlis, 2022)
The purpose of this study is to determine the effect of social media marketing on consumer consumption behaviour. The focus of this study is to determine whether the frequency of advertisement, social media fashion trends, influencer endorsements, and product brands have an effect on consumption behaviour among Malaysian youths. An online questionnaire that measures factors was constructed and disseminated to young Malaysians to acquire the data needed for this study. SEM-PLS is being used to evaluate the data. A conclusion has been drawn and this study also provided some recommendations for future research.